Combating the epigenome: epigenetic drugs against non-Hodgkin's lymphoma. (August 2013) - Hassler, Melanie R; Schiefer, Ana-Iris; Egger, Gerda
Non-Hodgkin's lymphomas (NHLs) comprise a large and diverse group of neoplasms of lymphocyte origin with heterogeneous molecular features and clinical manifestations. Current therapies are based on standard chemotherapy, immunotherapy, radiation or stem cell transplantation. The discovery of recurrent mutations in epigenetic enzymes, such as chromatin modifiers and DNA methyltransferases, has provided researchers with a rationale to develop novel inhibitors targeting these enzymes. Several clinical and preclinical studies have demonstrated the efficacy of epigenetic drugs in NHL therapy and a few specific inhibitors have already been approved for clinical use. Here, we provide an overview of current NHL classification and a review of the present literature describing epigenetic alterations in NHL, including a summary of different epigenetic drugs, and their use in preclinical and clinical studies.